2011
DOI: 10.1073/pnas.1115926109
|View full text |Cite
|
Sign up to set email alerts
|

Parallel up-regulation of the profilin gene family following independent domestication of diploid and allopolyploid cotton ( Gossypium )

Abstract: Cotton is remarkable among our major crops in that four species were independently domesticated, two allopolyploids and two diploids. In each case thousands of years of human selection transformed sparsely flowering, perennial shrubs into highly productive crops with seeds bearing the vastly elongated and abundant single-celled hairs that comprise modern cotton fiber. The genetic underpinnings of these transformations are largely unknown, but comparative gene expression profiling experiments have demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 58 publications
2
71
1
Order By: Relevance
“…Plant cell morphology is largely determined by the highly dynamic actin cytoskeleton [55]. In this study, we found that cytoskeletal proteins were highly differentially regulated during fiber development, which included actin and actin binding proteins profilin and annexin.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Plant cell morphology is largely determined by the highly dynamic actin cytoskeleton [55]. In this study, we found that cytoskeletal proteins were highly differentially regulated during fiber development, which included actin and actin binding proteins profilin and annexin.…”
Section: Discussionmentioning
confidence: 76%
“…In this study, we identified multiple cytoskeletal-related proteins that were differentially regulated, including the actin binding proteins, profilin and actin-depolymerizing factor (ADF). Profilins have been found to be expressed during early cotton fiber development [53,54,55], and when overexpressed in transgenic tobacco cells, they produced an elongated cell with thicker and longer microfilament cables [54,55]. We found that an isoform of profilin (A0A0B0PF49) was downregulated during secondary wall deposition (25 dpa) when compared to an earlier fiber development stage (15 dpa), while actin depolymerizing factor 7 (A1XJ44) was found to be upregulated in 15 dpa when compared to 10 dpa and downregulated in 25 dpa fiber when compared to 15 dpa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The domesticated cottons, which were independently domesticated, show the lint or the spinnable seed fibers that result from human selection. Comparative gene expression-profiling experiments demonstrated upregulation of profilin accompanying domestication in the species for which wild relatives are known (Bao et al 2011). Profilins are actin monomer binding proteins involved in cytoskeletal dynamics and in cotton fiber elongation.…”
Section: Cottonmentioning
confidence: 99%
“…The ATL family of RING finger proteins, which contain a RING-H2 domain, was first identified in Arabidopsis (Salinas-Mondragon et al 1999) and later found to be widely distributed in all plants, including 80 and 121 ATL genes in Arabidopsis and rice, respectively (Serrano et al 2006). Cotton is the world's largest and most vital source of renewable textile fiber (Bao et al 2011). G. arboreum and G. raimondii underwent whole-genome duplication events about 16.6 million years ago (Mya), and G. hirsutum (allotetraploid) emerged from hybridizations of A or D diploid ancestral species nearly 1.5 Mya (Li et al 2015).…”
Section: Rh2fe3 Genes Of Arabidopsis Rice and Cottonmentioning
confidence: 99%